Navigating between Real and Virtual Storyworlds. Bell, Alice, and Marie-Laure Ryan. Possible Worlds Theory and Contemporary Narratology, edited by Alice Bell and Marie-Laure Ryan, U of Nebraska P, 2019, 354 pp. - Livytska, Inna (Anafora, 2023)
Navigating between Real and Virtual Storyworlds. Bell, Alice, and Marie-Laure Ryan. Possible Worlds Theory and Contemporary Narratology, edited by Alice Bell and Marie-Laure Ryan, U of Nebraska P, 2019, 354 pp.